Implications of Good Corporate Governance and Cost Efficiency on Islamic Social Reporting (Case Studies on Islamic Banking Companies in Indonesia) - Abd Rohman Taufiq; Juli Murwani; Jenizar Utami (Politeknik Negeri Madiun, 2023)
The Islamic banking industry in Indonesia is experiencing very strong growth with the potential for Islamic financial assets of 99 billion, making Indonesia ranked 4th in the world in 2020. The issue of increasing Corporate Social Responsibility (CSR) sustainability disclosure has made the issue of Islamic Social Reporting a reality. (ISR) is also increasing. This study aims to examine the effect of Good Corporate Governance and cost efficiency on Islamic social reporting (ISR). The type of data in this study uses panel data taken using a time span of five years from the 2014-2020 period. The analysis technique used consists of classical assumption test, multiple linear regression analysis test and partial test (t). The results show that Good Corporate Governance has a negative and significant effect on Islamic Social Reporting (ISR). Meanwhile, cost efficiency has no effect on Islamic Social Reporting (ISR).